2008
DOI: 10.1039/b806869k
|View full text |Cite
|
Sign up to set email alerts
|

Intramolecular kinetic isotope effect in hydride transfer from dihydroacridine to a quinolinium ion. Rejection of a proposed two-step mechanism with a kinetically significant intermediate

Abstract: The intramolecular kinetic isotope effect (KIE) for hydride transfer from 10-methyl-9,10-dihydroacridine to 1-benzyl-3-cyanoquinolinium ion has been found to be 5-6 by both (1)H NMR and mass spectrometry. This KIE is consistent with other hydride transfers. It is inconsistent with the high intermolecular KIEs derived by fitting to a two-step mechanism with a kinetically significant intermediate complex, and it is inconsistent with the strong temperature dependence of those KIEs. We therefore reject the two-ste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…We demonstrated that isotopic perturbation of resonance is real, in a series of metal complexes . We measured the intramolecular KIE for hydride transfer from an NADH model to a quinolinium ion and found that it is inconsistent with the intermolecular IEs that had been claimed as evidence for a two‐step mechanism.…”
Section: Researchmentioning
confidence: 91%
“…We demonstrated that isotopic perturbation of resonance is real, in a series of metal complexes . We measured the intramolecular KIE for hydride transfer from an NADH model to a quinolinium ion and found that it is inconsistent with the intermolecular IEs that had been claimed as evidence for a two‐step mechanism.…”
Section: Researchmentioning
confidence: 91%
“…Since 1 H and 2 H are often used as good hydride donors, 2 + and 7 (MeO) + are often used as good hydride acceptors, , and the corresponding KIE self values of the three hydride self-exchange reactions in acetonitrile at 298 K have been determined, it is not difficult to get the KIE self values of any another hydride self-exchange reactions XH + X + →X + + XH in acetonitrile at 298 K as long as the KIE value of the related hydride cross transfer reaction that one reactant is one of 1 H, 2 H, 2 + and 7 (MeO) + (eqs –) and their extension can be determined in acetonitrile at 298 K. In this work, the KIE self values of 68 hydride self-exchange reactions (XH/X + ) in acetonitrile at 298 K (see Table ) were obtained from the KIE values of the corresponding 68 hydride cross transfer reactions in acetonitrile at 298 K according to eq . All of the latter values can be determined using the stopped-flow UV–vis method in our laboratory, and the detailed results are listed in Table . …”
Section: Determination Of Kieselfmentioning
confidence: 99%
“…In connection with our interest in hydrogen tunneling, the intramolecular KIE for hydride transfer from 10-methyl-9,10-dihydroacridine- d ( 42 - d ) to 1-benzyl-3-cyanoquinolinium ion ( 43 ) (Scheme ) was measured by NMR (and by mass spectrometry) . The result, k H / k D = 5–6, is a very ordinary and anticlimactic KIE, inconsistent with the unusually high intermolecular KIEs, attributed to tunneling, that were derived by fitting the kinetics of reactions of 42 and 42 - d 2 with 43 to a two-step mechanism with an intermediate complex .…”
Section: Primary Kinetic Isotope Effectsmentioning
confidence: 99%